Evaluation of Agronomic Traits and Severity of Foliar Disease of Three Commercial Hybrids and Five Advanced Triple Hybrids of Hard Yellow Maize - Cabascango-Paucar, Ruth Angélica; Valverde-Pérez, William Mauricio; Bolaños-Carriel, Carlos; Basurto-Zambrano, Julio César; García-Calderón, Erwin Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Field experiments were conducted to evaluate agronomic traits and response to foliar fungal diseases of five advanced triple hybrids of hard yellow maize (Zea mays L.) and three commercial hybrids. An A × B factorial experiment with eight treatments, four repetitions and the Tukey test was used to compare means of the treatments (P>0.05). The most limiting disease is rust. The agronomic characteristics of breeding lines: h1, h2, h3, h4 and h5 (triple hybrids) were evaluated and compared with h6, h7, and h8 (commercial hybrids). Field trials were conducted in two locations of Central Coast of Ecuador (Quevedo & Balzar). Both locations showed significant differences for agronomic traits; Balzar presented lower yield (6,205.46 kg ha-1) and greater severity of curvularia leaf spot (3.34 CIMMYT scale) compared to Quevedo (7,368.21 kg ha-1 and 2.47 CIMMYT scale). For hybrids, h6 had significantly lower yield (5,306.83 kg ha-1), compared to h5 (6,914.09 kg ha-1), h1 (7,211.80 kg ha-1), h3 (7,266.83 kg ha-1), and h8 (8,036.85 kg ha-1). Significant differences were also detected for the orthogonal comparison (INIAP hybrids) with 5,634.44 kg ha-1 and the promissory lines with 6,997.68 kg ha-1. The highest net profit was achieved with the hybrid h2 with USD 1,405.76 followed by the hybrid h1 with USD 1,385,92, obtaining a Benefit-Cost ratio of 2.32 and 2.30 respectively, which indicates that for each monetary unit invested, an additional USD 1.32 and 1.30 of profit was obtained for the two hybrids, respectively.